Answer: - 11x + 6y = - 13
Explanation:
The slope intercept form of a straight line is expressed as
y = mx + c
Where
m represents the slope of the line
c represents the y intercept
The given line passes through
(- 1, - 4) and (5, 7)
Slope = (y2 - y1)/(x2 - x1)
Slope,m = (7 - - 4)/(5 - - 1) = 11/6
To determine the y intercept, we would substitute x = - 1, y = - 4 and
m = 11/6 into y = mx + c. It becomes
- 4 = 11/6 × - 1 + c
- 4 = - 11/6 + c
c = - 4 + 11/6
c = - 13/6
The slope intercept equation is
y = 11x/6 - 13/6
The standard form equation of a line is
Ax + By = C
Multiplying both sides by 6, it becomes
6y = 11x - 13
- 11x + 6y = - 13